4R nitrogen management when integrating canola into semi‐arid wheat. Issue 3 (19th May 2017) - Pan, W.L.; Maaz, T.M.; Madsen, I.J.; Reese, M.; Hammac, W.A.; Wysocki, D.; Davis, J.B.; Wingerson, M.; Brown, J.
Abstract : Canola is a new crop for many inland Pacific Northwest U.S. wheat growers to consider for integration into their wheat‐dominated systems. Both crops have winter and spring varieties that can fill niches in different precipitation zones across the region, and they both efficiently extract available water to depths of 4 to 6 ft if soil depth allows. Yet, physiological and morphological differences dictate necessary changes in 4R N management approaches and recommendations when transitioning from wheat to canola. Additional differences in water and N use efficiency are also key factors that contribute to region‐specific N recommendations. And so, the saying goes in the inland Pacific Northwest that canola "is not your father's wheat." Earn 1 CEU in Nutrient Management by reading this article and taking the quiz at www.agronomy.org/education/classroom/classes/410